Macular Pigment Optical Density in the Elderly: Findings in a Large Biracial Midsouth Population Sample - Iannaccone, Alessandro (2007)
PURPOSE: To report the macular pigment optical density (MPOD) findings at 0.5° of eccentricity from the fovea in elderly subjects participating in ARMA, a study of aging and age-related maculopathy (ARM) ancillary to the Health, Aging, and Body Composition (Health ABC) Study. METHODS: MPOD was estimated with a heterochromatic flicker photometry (HFP) method in a large biracial population sample of normal 79.1 ± 3.2-year-old adults living in the Midsouth (n = 222; 52% female; 23% black, 34% users of lutein-containing supplements). Within a modified testing protocol, subjects identified the lowest and the highest target intensity at which the flicker sensation disappeared, and the exact middle of this “no-flicker zone” was interpolated by the examiner. RESULTS: An MPOD estimate was obtained successfully in 82% of the participants. The mean MPOD in our sample was 0.34 ± 0.21 (SD). The interocular correlation was high (Pearson’s r = 0.82). Compared with lutein supplement users, mean MPOD was 21% lower in nonusers (P = 0.013). MPOD was also 41% lower in blacks than in whites (P = 0.0002), even after adjustment for lutein supplement use. There were no differences in MPOD by gender, iris color, or history of smoking. CONCLUSIONS: Older adults in the Midsouth appear to have average MPOD and interocular correlation comparable to those in previous studies. Lutein supplement use and white race correlated with higher MPOD. No evidence of an age-related decline in MPOD was seen in the sample. The HFP method for the measurement of MPOD is feasible in epidemiologic investigations of the elderly, the group at highest risk of ARM.